Praktik Akuntansi Hijau pada Perusahan Tambang Nikel PT. Vale Indonesia Tbk. - Amalia, Rizki; Arseyani, Dede; Nuriatullah; Nurfitriani (Scimadly Publishing, 2024)
This study aims to analyze green accounting practices at the Nickel Mining Company PT Vale Indonesia Tbk. This research is qualitative research with a case study approach. The data used is the company's annual and/or sustainability report for 2020-2022. The results showed that the company has implemented green accounting quite well, but detailed details about environmental costs are not visible, either in the Annual report or in the Sustainability Report. The treatment of environmental costs that have been incurred is recorded as other expenses in the company's income statement. Sustainability performance at PT Vale Indonesia Tbk. is inseparable from the three triple bottom line categories, namely economic performance, environmental performance and social performance as a manifestation of green accounting. Green Accounting Practices provide effects or benefits in improving economic performance, environmental performance and social performance, but it is also undeniable that there are still several challenges regarding green accounting practices in the future.